MODELING AND SIMULATION OF BATTERY ENERGY STORAGE SYSTEM FOR VOLTAGE REGULATION IN SMART MICROGRID - Pratama Tjahja, Timotius
The use of energy from conventional power plants using non-renewable fossil fuels can be interrupted which leads to power outage. Therefore, to keep the availability of power at the grid, it must be complemented with a renewable power plant, a solar power plant can be one of the alternatives. Along with the development of technology, existing equipment, such as TEM (Transmission Electron Microscope) operating at CAS Building, is also sensitive to power quality, such as voltage stability. Fluctuating load power consumption will have an impact to voltage stability. The purpose of this thesis is to design a single phase smart microgrid with a Battery Energy Storage System (BESS) for regulating voltage. This thesis also aims to determine the parameters that exist in the battery inverter component using the droop control concept so that the BESS will supply reactive power which will make the voltage of the microgrid remain stable. The optimal parameter of BESS obtained is the optimum voltage tolerance range of the BESS, namely U1 = 194.91 V and U4 = 234.59 V and the deadband range on the droop control curve, namely U2 = 198 V and U3 = 231 V. BESS will control its reactive power output to stabilize the voltage with maintaining power factor values of 0.8 - 0.86 leading for low loads and 0.95 - 1 leading for high loads. The results of the simulation using the optimal parameters calculated in this study indicate that the voltage regulator system on SBPE can maintain voltage by Indonesian electrical standards. The simulation also shows enhancement on the power quality index, namely DSI (Discrete Severity Index) and SARFI (System Average RMS-variation Frequency Index) to 0 both in grid connected and islanded conditions.